2000
DOI: 10.1002/1529-0131(200010)43:10<2265::aid-anr14>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of anti-double-stranded DNA antibodies: The natural immune complex clearance mechanism

Abstract: Objective. To develop an in vitro model for investigating the mechanism by which autoantibodies in immune complexes (ICs) that are bound to primate erythrocytes via antigen-based heteropolymers (AHPs) are cleared from the circulation and localized to the liver.Methods. IgG anti-double-stranded DNA (antidsDNA) antibodies in ICs with dsDNA were bound to human erythrocytes via complement receptor 1 (CR1) either by opsonization with normal human serum as a complement source or through the use of an AHP, which cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 60 publications
4
22
1
Order By: Relevance
“…Indeed, we observed that the furin inhibitor CMK and the metalloprotease inhibitor 1,10-phenanthroline demonstrated only marginal inhibition of FcγR induced BLyS/BAFF shedding (results not shown). Interestingly, a similar protease-resistant FcγRI induced cleavage of CR1 (CD35) has been observed (40)(41)(42).…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, we observed that the furin inhibitor CMK and the metalloprotease inhibitor 1,10-phenanthroline demonstrated only marginal inhibition of FcγR induced BLyS/BAFF shedding (results not shown). Interestingly, a similar protease-resistant FcγRI induced cleavage of CR1 (CD35) has been observed (40)(41)(42).…”
Section: Discussionsupporting
confidence: 55%
“…Whether the localized mAb 7G6 is held on FDC by Fc␥R (30,31), or in part by FDCassociated CR1/2, or by CD23, which binds CR2 in primates (59,60), is not revealed presently, but this question may be addressed in appropriate knockout animals. Support for proteolytic release of extracellular B cell CR1/2 is also found in studies that indicated cleavage of a structurally related protein, primate E CR1, is required for the transfer of CR1-bound IC from E to acceptor cells (61)(62)(63). In fact, in diseases associated with C activation and IC processing, levels of both E CR1 and B cell CR2 are reduced substantially (47, 64 -66).…”
Section: Transfer To Fdcs Appears To Be Mediated By Extracellular Promentioning
confidence: 84%
“…The transfer mechanism could be driven by a higher number of CR1 copies on the monocyte than on the RBCs (63) or by the close juxtaposition of the macrophage to the RBC-bound ICs that leads to macrophageassociated protease cleavage of CR1 and a release of the IC from the RBC (64). It is possible that instability of RBC membranes may occur during transfer of CR1-bound ICs from erythrocytes to acceptor phagocytic cells via Fc receptors (64,65) and thus trigger RBCs to shed MPs.…”
Section: Cd235mentioning
confidence: 99%